Benefiting from Publicly Funded Pre-competitive Research – Differences between Insiders and Outsiders - Verena Eckl; Dirk Engel (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This article contributes to the debate on the systemic effects of technology policy by investigating knowledge spillovers of pre-competitive publicly funded Industrial Collective Research (ICR) in Germany. The ICR aims to compensate for obstacles faced by SME in carrying out research and development (R&D). Using data from 911 firms surveyed in 2006, the results show that non-participants use ICR results to a significant extent. However, almost all users in the group of non-participants are engaged in other publicly funded or non-publicly funded collaborative research projects with research institutes affiliated to ICR.
Keywords: O38; H59; D21; C25; 330; Technology policy Evaluation; public R&D subsidies; pre-competitive research; spillovers; Forschungs- und Technologiepolitik; Forschungssubvention; Wirkungsanalyse; Wissenstransfer; Klein- und Mittelunternehmen; Forschungskooperation; Deutschland